Evaluation of current strategies for surveillance and management of donor‐specific antibodies: Single‐center study. Issue 7 (7th June 2018) - Sullivan, Daniel; Ahn, Chul; Gao, Ang; Lacelle, Chantale; Torres, Fernando; Bollineni, Srinivas; Banga, Amit; Mullins, Jessica; Mohanka, Manish; Ring, Steve; Wait, Michael; Peltz, Matthias; et al.
Abstract: Background: Although the presence of donor‐specific antibodies (DSA) is known to impact lung allograft, limited data exist regarding DSA management. Methods: We did a retrospective study at our center evaluating DSA management in adult lung transplant recipients undergoing lung transplantation between January 1, 2010 and June 30, 2014. Study follow‐up was completed through October 2017. All recipients were stratified into 2 groups based on the presence or absence of DSA. Those with DSA were evaluated for the impact of treatment of DSA. The primary outcomes were postlung transplant survival and freedom from bronchiolitis obliterans syndrome (BOS), subset of chronic lung allograft dysfunction (CLAD). Simon‐Makuch method was used to estimate overall survival and BOS‐free survival to account for DSA as time‐dependent covariate. Survival differences between the groups were analyzed using time‐dependent Cox proportional hazards model. Results: Sixty‐four percent of 194 total subjects developed post‐lung transplant DSA. Overall survival was different with worse survival in the DSA positive group that never cleared DSA ( P = .002). BOS‐free survival was lower, but did not reach significance in this group. Response to treatment was poor, with only 12 of 47 (25.5%) who received treatment demonstrating clearance of DSA. Conclusions: Donor‐specific antibodies prevalence is high after lung transplantation. Clearance of DSA correlated with improved outcomes. Current therapeutic strategies against DSA are relatively ineffective. Multicenter collaborative studies will be required to evaluate current treatment strategies and other innovative modalities.